Multimodality imaging of chronic tophaceous gout - R. Piccazzo; A. Denegri; A. Muda; L.M. Sconfienza; F. Paparo; E. Aleo; M.A. Cimmino (PAGEPress Publications, 2011)
The diagnosis of gout is usually based on clinical presentation and laboratory findings. Imaging plays a role in the assessment and grading of articular damage related to chronic, long-standing disease, which is characterized by granulomatous synovitis, tophi, and erosions. Multimodality imaging of chronic tophaceous gout may be useful in clinical practice for a variety of purposes, including assessment of disease-related anatomical changes and monitoring of articular and soft-tissue lesions over time, especially in response to urate-lowering therapy. Radiography remains the primary imaging technique. Ultrasonography may detect monosodium urate crystals on cartilage, is helpful to assess small joint effusion, to guide to joint aspiration, and to evaluate the volume of tophi. Computed tomography is considered to be more sensitive than plain radiography in the detection and evaluation of cortical bone erosions associated with tophi. MRI represents the only imaging modality which provides visualization of bone marrow oedema associated with erosions and may be useful to characterize and distinguish tophi from other soft tissue nodules.